Correction: Almutary et al. Development of 3D-Bioprinted Colitis-Mimicking Model to Assess Epithelial Barrier Function Using Albumin Nano-Encapsulated Anti-Inflammatory Drugs. Biomimetics 2023, 8, 41 - Abdulmajeed G. Almutary; Abdullah M. Alnuqaydan; Saleh A. Almatroodi; Hamid A. Bakshi; Dinesh Kumar Chellappan; Murtaza M. Tambuwala (Biomimetics)
In the original publication [...]